Weed Control in Irrigated Corn with Combinations of Corvus, Balance Flexx, Capreno, Laudis, Harness, Atrazine, Glyphosate, Dual, and Diflexx - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
Most preemergence treatments followed by postemergence treatments provided better Palmer amaranth control than preemergence treatments alone or early postemergence treatments alone (Table 2). The better treatments provided good control of Palmer amaranth, kochia, Russian thistle, crabgrass, green foxtail, and shattercane. All treatments elevated yield over the untreated control.
Keywords: weed science; weed control; irrigated corn; shattercane; green foxtail; crabgrass; kochia; Palmer amaranth; Russian thistle; preemergence herbicide; postemergence herbicide; Corvus; Balance Flexx; isoxaflutole+a safener; Capreno; tembotrione+thiencarbazone-ethyl; Laudis; tembotrione; Harness; acetochlor; atrazine; glyphosate; Dual; Difless; dicamba; broadleaf control; tank mix; broad-spectrum weed control